Increases in platelet and red cell counts, blood viscosity, and arterial pressure during mild surface cooling: factors in mortality from coronary and cerebral thrombosis in winter. Issue 6456 (24th November 1984) - Keatinge, W R; Coleshaw, S R; Cotter, F; Mattock, M; Murphy, M; Chelliah, R
Abstract : Six hours of mild surface cooling in moving air at 24 degrees C with little fall in core temperature (0.4 degree C) increased the packed cell volume by 7% and increased the platelet count and usually the mean platelet volume to produce a 15% increase in the fraction of plasma volume occupied by platelets. Little of these increases occurred in the first hour. Whole blood viscosity increased by 21%; plasma viscosity usually increased, and arterial pressure rose on average from 126/69 to 138/87 mm Hg. Plasma cholesterol concentration increased, in both high and low density lipoprotein fractions, but values of total lipoprotein and lipoprotein fractions were unchanged. The increases in platelets, red cells, and viscosity associated with normal thermoregulatory adjustments to mild surface cooling provide a probable explanation for rapid increases in coronary and cerebral thrombosis in cold weather. The raised arterial pressure and possibly cholesterol concentration may contribute to slower components of the increased thrombosis.